(untitled) (Journal of Student Affairs in Africa, 2021)
Elections in fledgling democracies are punctuated by perceived and observed cases of vote buying otherwise also called electoral clientelism - regarded as a major threat to democratic consolidation. Notions of vote buying are variously captured in the burgeoning literature on democracy, but the ongoing scholarly discussions have failed to engage some growing contemporary trends that also contribute significantly to sustaining the culture of vote buying in intra-party, local and national elections. In our analysis of recent intra-party elections in Ghana, we argue that vote buying has become more complexand more pronounced - and the proliferation of the phenomenon is aided by student campus politics (particularly at the various tertiary institutions), which directly feed into national politics. Following this stance, the article concludes with a recommendation that further empirical research be conducted byscholars and policymakers to fully examine the reinforcing role of campus politics in electoral clientelism during intra-party elections and, by extension, national elections.